First report of pathogenic Leptospira spp. in Tadarida brasiliensis bats (family Molossidae) and Eptesicus furinalis (family Vespertilionidae) of Argentina. New host species in this country? = Primer reporte de Leptospira spp. patógena en murciélagos Tadarida brasiliensis (familia: Molossidae) y Eptesicus furinalis (familia: Vespertilionidae) en Argentina. ¿Nuevas especies hospedadoras en el país? - Saraullo, Vanina Rosa; Grune Loffler, Sylvia; Pastorino, Florencia; Watanabe, Olivia; Alonso, Maria Laura; Hamer, Micaela; Moreira, Cecilia; Martinez, Mara Leila; Martinez, Gustavo; Brihuega, Bibiana Felicitas (Elsevier, 2022)
Leptospirosis is an endemic disease caused by Leptospira spp., a bacterium that affects animals and humans. In recent years, the number of reports of leptospirosis in wild animals has increased, which highlights the need to study the infectious agents in these animals. In this study, a duplex PCR for the detection of leptospiral DNA was performed on 50 kidney samples from bats, and a MAT (Microscopic Agglutination Test) for serological detection of anti-leptospiral antibodies was applied to 47 serum samples from bats from different regions of Buenos Aires Province, Argentina. DNA was extracted using Chelex-100 and duplex PCR was performed by targeting the detection of genes secY and flaB, of pathogenic Leptospira spp. Of the 50 kidney samples, 3 were positive for Eumops sp. and Tadarida brasiliensis by duplex PCR. Of the 47 serum samples, 12 were positive for different serovars: Leptospira interrogans serovars Icterohaemorrhagiae, Cynopteri and Bataviae, and Leptospira borgpetersenii serovar Ballum. This is the first report of the detection of pathogenic leptospires by serology in bats belonging to the T. brasiliensis and Eptesicus furinalis species in Argentina. In addition, this is the first report of the detection of pathogenic leptospiral DNA by PCR in T. brasiliensis species. The detection of Leptospira spp. in these wild animals shows that they may play an important role as wildlife reservoirs of leptospires.